2021
DOI: 10.1101/2021.05.20.21257181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and experimental factors that affect the reported performance characteristics of rapid testing for SARS-CoV-2

Abstract: Tests that detect the presence of SARS-CoV-2 antigen in clinical specimens from the upper respiratory tract can provide a rapid means of COVID-19 disease diagnosis and help identify individuals that may be infectious and should isolate to prevent SARS-CoV-2 transmission. This systematic review assesses the diagnostic accuracy of SARS-CoV-2 antigen detection in COVID-19 symptomatic and asymptomatic individuals compared to RT-qPCR, and summarizes antigen test sensitivity using meta-regression. In total, 83 studi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 110 publications
2
5
0
Order By: Relevance
“…Therefore, these findings regarding the variability in RAT sensitivity, when stratified by the presence or absence of COVID-19 symptoms, are not surprising given that symptomatic individuals are typically associated with specimens that have a higher viral load. The results here are consistent with previous studies that have shown better sensitivity of SARS-CoV-2 RATs when specimens are obtained from symptomatic individuals ( 16 , 18 ). However, although RAT sensitivity is somewhat reduced when compared to molecular-based testing, several drawbacks are associated with molecular testing including limitations in specimen processing capacity ( 33 , 34 ), prolonged turnaround time (at best 24 hours when sample shipment is considered), and the need for dedicated staff and automated platforms; all of which can limit turnaround time and impede optimized patient management ( 35 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, these findings regarding the variability in RAT sensitivity, when stratified by the presence or absence of COVID-19 symptoms, are not surprising given that symptomatic individuals are typically associated with specimens that have a higher viral load. The results here are consistent with previous studies that have shown better sensitivity of SARS-CoV-2 RATs when specimens are obtained from symptomatic individuals ( 16 , 18 ). However, although RAT sensitivity is somewhat reduced when compared to molecular-based testing, several drawbacks are associated with molecular testing including limitations in specimen processing capacity ( 33 , 34 ), prolonged turnaround time (at best 24 hours when sample shipment is considered), and the need for dedicated staff and automated platforms; all of which can limit turnaround time and impede optimized patient management ( 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although reflex RT-PCR testing was not performed for every RAT result, the reflex RT-PCR test results that were obtained showed a high percent (93.1%) agreement with RAT results from the total population. Overall, the results here are consistent with the general performance characteristics of SARS-CoV-2 RATs that have been demonstrated previously ( 16 , 18 ). Depending on the assumption for reflex RT-PCR testing that was applied, the sensitivity value for the RAT was either 77.2% (Assumption 1) or 85.6% (Assumption 2) in the symptomatic population, which overlaps with the sensitivity estimate [84% (95%CI: 67%, 93%)] listed for symptomatic individuals in Veritor's instructions for use ( 23 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations